Next year in Beirut?: Lebanese Jewish identity and memory in the Mediterranean francosphère. Issue 1 (July 2017) - Watson, Robert
Abstract : Despite a few scholarly and popular contributions, the story of the Jews of Lebanon remains outside dominant narratives of the country's recent past and the recent revival of memory studies on the Jews of the Arab world. The Lebanese Jewish story does not fit the chronology of other populations which saw major declines after the creation of Israel in 1948, as Beirut in particular became a home for other displaced communities. Exploring the richness of recent documentary films on the subject, the present study argues that the very category of 'Lebanese Jew' became increasingly difficult to articulate after Israel's creation, despite Jews' profound participation in the Lebanese mosaic and Beirut's geography and cultural life. Examining the nuances in narratives of why Jews left, both from their own perspectives and from those of other Lebanese, we find that the efforts to recreate the memory of the community are very much connected with those to articulate a national project for all Lebanese.